Estimated Divergence Times of Lecanicillium in the Family Cordycipitaceae Provide Insights Into the Attribution of Lecanicillium - Zhou, Ye-Ming; Zhi, Jun-Rui; Qu, Jiao-Jiao; Zou, Xiao (Frontiers in Microbiology, 2022)
Background The genus Lecanicillium W.Gams & Zare is a recognized insect pathogen but members of the genus have been found parasitizing various hosts including arthropods, nematodes, plants, and fungi. The new classification system for fungi proposed to reject Lecanicillium and transfer some of the species to the genus Akanthomyces. However, the attribution problem of most species in the original genus Lecanicillium remains unsolved. The current study aimed to improve understanding of the pivotal internal phylogeny in Lecanicillium by estimating the divergence times of Lecanicillium to provide additional insights into the status of this genus within the family Cordycipitaceae. Results Dating analyses support the supposition that the ancestor of Lecanicillium was in the Cretaceous period (84.36 Mya, 95% HPD: 72.12–94.74 Mya). After originating from a common ancestor, eight clades of Lecanicillium were derived and evolved independently in parallel with other genera of Cordycipitaceae. Based on the clear divergence age estimates, Lecanicillium clade 8 originated earlier as an independent group in the Cretaceous period (75.61 Mya, 95% HPD: 63.31–87.54 Mya), while Lecanicillium clades 1–7 originated later as an independent group in the boundary of the Cretaceous and Paleogene periods (64.66 Mya, 95% HPD: 52.75–76.74 Mya). Lecanicillium huhutii formed an independent branch in a polytomy together with a clade containing Lecanicillium tenuipes (BI posterior probabilities 1, ML bootstrap 100%). Conclusion The pivotal internal phylogeny, origin, and evolutionary history of Lecanicillium in the family Cordycipitaceae were investigated. Phylogenetic and morphological analyses indicated that there are eight representative clades (four representative branches of evolutionary history), including clade 1 (members have a relatively uniform sporulation structure comprising globose heads with a higher number of conidia), clade 8 (including all members of Gamszarea), clades 2–5 (the differences of the divergence time estimations were smaller compared with other clades), and clade 6–7 (members are close to Gibellula, Hevansia, and Ascopolyporus). Based on the above findings, a novel spider-pathogenic fungus, Lecanicillium huhutii, is described. All other species in Lecanicillium clade 1 (Lecanicillium araneogemum, L. nodulosum, L. pissodis, and L. uredinophilum) should be transferred to the genus Akanthomyces. Furthermore, the monotypic genus Parengyodontium should be merged with the genus Gamszarea. More novel species need to be discovered to thoroughly resolve the attribution problem of Lecanicillium. Finally, no major lineages of Lecanicillium were correlated with the nearby Cretaceous-Tertiary extinction event, indicating that the diversity of Lecanicillium is more likely to be caused by long-term environmental adaptation and coevolution with insects rather than by dramatic extinction events.